Răspuns :
Răspuns:
Explicație pas cu pas:
a ) ( x - 36 ) : 36 = 36
x - 36 = 36 x 36
x - 36 = 1296
x = 1296 + 36
x = 1332
b) ( 27 + 2 x ) : 27 = 27
(27 + 2 x ) = 27 x 27
27 +2 x = 729
2 x= 729 - 27
2 x = 702
x = 702 : 2
x = 351
c ) ( 650 - x ) x 65 = 4225
650 - x = 4225 : 65
650 - x = 65
x = 650 - 65
x = 585
Răspuns:
Explicație pas cu pas:
a)
(x-36)÷36=36
x - 36 = 36 x 36
x - 36 = 1296
x = 1296 + 36
x = 1332
b)
(27+2x)÷27=27
27 + 2x = 27 x 27
27 + 2x = 729
2x = 729 - 27
2x = 702
x = 702 : 2
x = 351
c)
(650-x)×65=4225
650 - x = 4225 : 65
650 - x = 65
x = 650 - 65
x = 585